FACTORS RELATED TO THE INCIDENCE OF HIV/AIDS AMONG SHEMALE IN SURABAYA, INDONESIA - Ridhwan Biosia Wiratama; Samsriyaningsih Handayani; Soetjipto Soetjipto (Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: Acquired Immunodeficiency Syndrome (AIDS) is one of the diseases that cause death in the world caused by the Human Immunodeficiency Virus (HIV). Since it was first discovered in 1987 until December 2017, the number of person with AIDS was 102,667, and the number of person with HIV infections was 280,623. HIV/AIDS cases in East Java occupy the second highest position in Indonesia. Surabaya is the first city in East Java with 934 HIV cases in 2017. Shemale is one of the groups at risk of getting HIV/AIDS with prevalence was 24.82%. Objective: The purpose of this study was to analyze the factors that influence shemale related to the incidence of HIV/AIDS in Surabaya. Materials and Methods: This study was an analytic research using a cross sectional approach. The subject was 80 shemale respondents. Data were collected using questionnaires then analyzed using Chi-square test, with α=0.05. Results: The highest age group was 42-46 years (22.5%), the last level of education was dominated by high school (41.3%), and the most types of work were private employees (47.4%). There was no correlation between predisposing factors in the form of knowledge about HIV/AIDS and respondent's HIV status (p=0.729), there was no correlation between enabling factors in the form of condoms and respondent's HIV status (p=0.624), there was no correlation between the reinforcing factor in the form of family support with the HIV status of the respondent (p=0.674) and there was no correlation between preventive behavior and the HIV status of the respondent (p=0.540). Conclusion: The need for support between shemales for the dangers of HIV/AIDS and shemale should be more aware of their own health and environment with their social patterns.